Caracterização fenológica e morfológica de plantas e qualidade pós-colheita de frutos de acessos de cambuizeiro (Myrciaria floribunda O. Berg) do banco ativo de germoplasma do CECA - UFAL - Santos, Everton Ferreira dos (2018)
The species Myrciaria floribunda (West ex Willdenow) O. Berg, Myrtaceae, popularly known as Cambui, presents a natural distribution in areas of sandy restingas of the southern coast of Alagoas, mainly in the municipalities of Piaçabuçu and Penedo. It is a native fruit of potential economic value, its fruits are much appreciated both in natura and processed. The plant is used as medicinal, ornamental and in urban afforestation projects. However, due to the disordered urban and agricultural occupation, the species suffers considerable risk of being extinct in Alagoas, needing studies that aim at maintaining its genetic diversity in the State. The objective of this study was to evaluate the phenological and morphological aspects of plants and to perform the physical and physicochemical characterization of the fruits of cambuizeiro accesses from the Active Bank of Germplasm of the CECA / UFAL. In the phenological and morphological study carried out in the BSC-Cambui of the CECA / UFAL, in a population of 195 accessions, foliage, flowering and fruiting phenophases were observed through a semi-quantitative class scale proposed by Fournier (1974) and activity index. In the morphological characterization some vegetative and botanical morphological descriptors of the access population were obtained. The physical and physico-chemical characterization was performed in 11 random accessions, in relation to fruit weight, seed weight, longitudinal and transverse diameter of the fruit, seed diameter, total solids, total acidity, total solids / total acidity ratio, vitamin C, carotenoids, anthocyanins, flavonoids, total pectin and soluble. The results were submitted to descriptive statistical analysis, obtaining the minimum, mean and maximum values, standard error of the mean and coefficient of variation, and the means compared by Scott-Knott's cluster test at 5% probability. The Pearson correlation coefficient was calculated between the variables, and the significance was verified by the t test (P> 0.01). Foliar change occurred throughout the evaluation period, with higher intensity at the end of the rainy season and early dry season. The highest flowering peaks occurred at the end and beginning of the dry season. The fruiting occurred in the months of greater precipitation, with peaks in the months of May, August and December. The population presented considerable variability as to the determined morphological descriptors, leading to the formation of groups with distinct characteristics among the plants. There was a significant and positive correlation between the morphometric parameters with the diameter at the soil level (DNS) and height of the plant (AP). Significant differences were observed between the accesses for the physical and physical-chemical parameters determined, also leading to the formation of groups with different quality characteristics. There is a correlation between the accesses for the quality attributes evaluated. In general, the accesses evaluated presented variability among the evaluated parameters, subsidizing the selection of accesses through a single superior characteristic or concomitantly with others.